Synchronous mucinous cystadenoma ovary, leiomyoma uterus and mucinous adenocarcinoma cervix infiltrating into uterine leiomyoma: a rare case report - Rawal, Gireesha; Zaheer, Sufian; Yadav, Amit Kumar; Sahani, Neelam; Dhawan, Indrani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The overall incidence of synchronous female genital tract malignancies is 0.63%. The most frequently observed synchronous neoplasms are those of the ovary together with the endometrium. Cervical and ovarian malignancies are exceedingly rare. We present the case of a female patient who complained of abdominal distention and pain abdomen. A cervical pap smear was performed, and it showed inflammation and atrophic changes. USG abdomen revealed findings consistent with pyometra. Repeated dilatation and curretage for resolving the pyometra was attempted, but it yielded mucinous fluid only. Another USG abdomen was done, which showed a cervical growth. The patient was taken up for staging laparotomy. Per operatively, no growth could be identified in the cervix. However, dense adhesions of the cervix with the bladder were present. A bilateral salpingo-oophorectomy specimen was sent for intraoperative cytology, and showed mucinous cystadenoma, ovary. Further, the completion total hysterectomy specimen was sent for histopathology. Sections showed adenocarcinoma, cervix and leiomyoma, uterus. The cervical adenocarcinoma showed infiltration into the uterine leiomyoma. Thus, we document a very rare case involving a patient who presented with three coexistent tumours involving bilateral ovaries and uterus. To our knowledge, this is the first reported case of the combination. Accurate diagnosis as separate independent primary tumours or as primary tumour associated with its metastasis, and identification the site of origin in secondary tumours has important prognostic implications and is necessary for appropriate staging and treatment.